A participatory SWOT analysis on water, sanitation, and hygiene management of disabled females in Dhaka slums of Bangladesh. (5th July 2022) - Nowreen, Sara; Chowdhury, Md. Arif; Tarin, Nusrat Jahan; Hasan, Md. Robiul; Zzaman, Rashed Uz
Abstract: Rampant slum growths add more barriers to scaling up sustainable WASH facilities coupled with safe MHM amenities for megacities. On top of inequalities in accessing to WASH provision, MHM sensitivity to the needs of disabled girls or women is commonly denied. Low-income community case studies from the megalopolis of Dhaka, Bangladesh, capture multi-faceted links between disabled-female's agony and hygiene issues. Layers of discrimination are faced starting from no education after puberty to becoming a family burden. An overall assessment was further extended to identify SWOT for water and sanitation access to hygiene and MHM practices from the gender perspectives applying several mixed-method participatory approaches. Insufficient government support amount, inadequate pipeline water supplies, inconvenient infrastructures, and pricey hygiene products are considered as key weaknesses. Immediate demands include policies for empowerment via training, education coupled with caring services, and adequate, affordable, and disabled inclusive MHM amenities at public places. Finally, the analyses suggest community choices classifying recommendations into three broad categories, namely policy, intervention, and research to serve policymakers and gender experts in identifying potential measures to achieve the global targets of SDGs 3, 5, 6, and 10. Among many solutions, income opportunity via non-governmental loans for caretakers was proposed by most. HIGHLIGHTS: Available amenities are not designed to tackle the complex support needs of disabled-females. Expensive menstrual commodities are often barriers to self-dependency. Immediate demand includes empowerment via training and/or entrepreneurship. A facilitative support worker at school is highly recommended. Running Theory of Change Workshops is necessary to break social taboos towards MHM and females with disability. Graphical Abstract